Varas federais de execução fiscal: um retrato do poder judiciário - Moraes, Luiz Antonio Pazos (2002)
This work presents a study about the federal judiciary and in particular about the creation of specialized courts in fiscal execution in Rio de Janeiro. The bibliography research includes an approach to administrative theory, the formation of the State and the particular procedure of the fiscal execution, the field research tries to describe the reality of the courts specialized in fiscal execution with the position of the magistrate, attorney and public servant. The results of the analysis is directed to show the federal judiciary and in particular the creation of specialized jurisdiction.